EKONOMI INDUSTRI PANGAN DAN KEBIJAKAN PENDUKUNGNYA - Rosadi, A. Husni Y. (FEB Universitas Sam Ratulangi Manado, 2023)
The research aims to analyze the contribution of the food industry to the economy and its supporting policies. The method used is a quantitative descriptive method, with secondary data from the Central Statistics Agency (BPS), the Ministry of Trade, and the Ministry of Industry. Data is processed and analyzed based on the relationship between variables. The analysis results show that the food industry's contribution to the national economy is the highest compared to other industries. Superior food products such as vegetable oil (CPO), marine products (fish, shrimp, processed fish), and plantations (coffee, tea, spices) provide a surplus balance in trade. Meanwhile, potential products such as sugar, food dregs, grains, milk, butter, eggs, and animal meat are still in a large deficit. Policies to strengthen the food industry have been issued, but they are still industry sectoral, not involving many other stakeholders such as other ministries, R&D institutions, universities, business actors, and the community.